Поврзаност на HLA и ризикот за развој на антиинтерферонски антитела кај пациенти со мултипла склероза третирани со интерферон бета - Бошковски, Бојан (Медицински факултет, УКИМ, Скопје, 2021)
Multiple sclerosis (MS) is common inflammatory disease of the central nervous system (CNS) and the hallmark is demyelination of the axons. Demyelination affects the cerebrum. Cerebellum, spinal cord and optic nerves. Multiple sclerosis is a leading cause of nondramatic disability in young population of 20-40 years of age. Genetic factors have a major role for MS development, especially HLA alleles. Interferon beta (IFNB) is a first line of treatment for MS. IFNB is a protein molecule that induces an immune response and development of antiinterferon binding antibodies (BAB). Aim of this study was to determine the percentage of patents with interferon beta BAB, to evaluate the influence of HLA alleles for BAB development and to evaluate the risk of HLA alleles for development of MS. Secondary endpoints were to determine of treatment duration will influence on BAB development and risk of HLA alleles for prolonged P100 wave of visual evoked potentials (VEP). In this study we have included 132 patients with MS treated with IFNB-1a 22 mcg and IFNB-1b 8MIU subcutaneously (SC) and IFNB-1a 30 mcg intramuscularly (IM) with a treatment duration of at least 2 months prior the start of the study. The study was conducted from 2015 to 2019. Our control group consisted of 1418 healthy individuals listed in the Institute of Immunology and Human Genetics and Macedonian Registry for Bone Marrow Donors. In all patients were tested for BAB antibodies with ELISA method. According to BAB titer were divided in two groups: ВАВ >50 pg/ml as a positive and ВАВ <50 pg/ml as a negative for BAB. All patients were genotyped for HLA class one alleles A, B, C and class II alleles DRB1 and DQB1. DNA was isolated and amplificated in a thermoshaker, PCR method was used with an n Olerup SSP kit for HLA DR-DQ alleles. PCR products were visualized on a 2% agarose gel. In a 70 patients VEP P100 wave was measured in two consecutive measurements with a four channel EMG/EP Keypoint machine with a standard silver electrodes From the results of this study we can see that 71 of the patients with MS were tested positive for BAB, and 61 were negative for BAB. Mean titer of BAB in patients treated IM with IFNB - 1a was 402,2 pg/ml and the BAB titer for IFNB - 1b 394,0 pg/ml, in the group of patients treated with IFNB - 1a SC BAB titer was 82,9 pg/ml which was statistical y significant. In patients treated with IFNB intramuscularly we did not confirmed statistically significant difference between BAB positive and BAB negative patients. In the group treated subcutaneously with Interferon β - 1b 78,4% were BAB positive and 21,6% were BAB negative and that was significant difference (P<0,05). The group treated with Interferon β - 1a, 28,2% were BAB positive and 71,8% were BAB negative (P<0,05). Patients treated SC with Interferon β - 1a had 0,3 (OR=0,317) times less risk for BAB development compared to IM Interferon β - 1a and) 0,1 times less risk compared to Interferon β – 1b IM (OR=0,108). We did not conform statistical significance between treatment duration ad risk for BAB development. We confirmed HLA alleles to be either risk or a protective фацотр фор МС девелопмент. HLA allele HLA-A*02 has a protective role for MS development (P=0,00283, OR = 0,652) and HLA-A*03 was a risk factor for MS (P=0,0444, OR = 1,602) compared to control group. We confirmed HLA-B*44 to a protective allele (P=0,0469, OR=0,49532) compared to control group. Alleles HLA-DRB1*15 and DQB1*06 were conformed as a risk alleles for MS development compared to the control group (P<0,0001, OR = 2,945, P < 0,0001, OR = 1,9878 respectively). The allele HLA-DQB1*03 was confirmed as a protective allele for MS (P=0,0004, OR = 0,51634) compared to the control group. We have not confirmed HLA risk for BAB development. Allele HLA-A*11 play as a protective allele and reduces the risk for prolonged P100 wave (P=0,000183, OR =0.1138). According to these results we conclude that more than 50% of the patients treated with IFNB are positive for BAB. Treatment duration did not influence BAB development. Alleles HLA-A*02, HLA-B*44, HLA-DQB1*03 have a protective role for MS development and alleles HLA-A*03, HLA-DRB1*15 и HLA-DQB1*06 are risk alleles for MS development. Carriers of the HLA-A*11 have lower chances to develop prolonged P100 which can be assumed to have slower disease progression.
Докторска дисертација одбранета во 2021 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Весела Малевска-Ивановска.
Keywords: multiple sclerosis, interferon beta, binding antibodies, HLA